Financial evaluation of intensive farming (SRI) method and forecasting farmers' adoption of this method: دراسة استطلاعية لعينة من العاملين في بعض الوحدات الاقتصادية المدرجة في سوق العراق للأوراق المالية (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aimed to evaluate the financial aspects of the transfer of intensive agricultural technologies (SRI) using the financial evaluation criteria for this aspect. The research problem started from the problems of rice cultivation in Iraq, as the cultivated areas of this crop decreased due to the decrease in water quotas. Therefore, cultivation methods must be used that reduce the use of water as well as It reduces costs and increases revenues. Therefore, it was necessary to evaluate the transfer of intensive cultivation technologies (SRI), as it is an economical method of using water in rice cultivation. The results of the financial evaluation of the Amber 33 variety (NPV, IP, IRR) showed that growing this variety in this way has economic feasibility, as it reached (13% - 1.07 - 344.70). These values ​​indicate the economic feasibility of this. As for the jasmine variety, its results were as follows (22%). (16578.37, 1.47), which is a good indicator of the acceptance of investment in these items, and means that the farms are expected to achieve economic profit. As for the results of the ADOPT analysis, it is expected that 11% of album farmers will be able to adopt intensive rice cultivation (SRI) after 5 years, and this percentage will increase after 10 years to reach 32% and reach the peak of adoption after 19.4 years by 40% of farmers, which is An acceptable percentage, as farmers adhere to the traditional farming method and do not like to risk changing their farming method, especially for rice crops, from the wet method to the dry method. Keywords: present value, internal rate of return.